Pengaruh Disiplin Kerja, Lingkungan Kerja dan Budaya Kerja Terhadap Kinerja Pegawai Di Kantor Pelayanan Pajak - Chairul Masri Lubis; Coory Audhita Tampublon; Juan Amanda Simanjuntak; Irwandi Lubis; Mohammad Ika Yazuar; Safrida Safrida; Nilawati Nasti; Ismail Nasution (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
This study aims to determine the Effect of work discipline, work environment and work culture appraisal partially and simultaneously on the performance of employees work in the Kantor Pelayanan Pajak Pratama Binjai. The study was conducted at the Kantor Pelayanan Pajak Pratama Binjai Jalan Jambi No.1, Rambung Barat, Binjai Selatan., Kota Binjai, Provinsi Sumatera Utara, kode pos 20722, with a population of 101 people, and a study sample. of 50 people. The data analysis technique used is multiple regression analysis using the IMB Statistics computer program for Product and Service Solution (SPSS) version 24. Based on the analysis results obtained work discipline has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Binjai, this is supported by the results of t count analysis > t-table (3,223 < 2,014) at n = 50 at 95% significance level. Work environment has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Binjai, this is supported by an analysis of t count > t-table (3,992 > 2,014) at n = 50 at 95% significance level. Work culture appraisal has a effect on the performance of employees work of the Kantor Pelayanan Pajak Pratama Binjai, this is supported by an analysis of t count >-table (11,210 > 2,014) at n = 50 with a significant level of 95%.Value of F-count> F table (56,432 > 2,81) This states that together (multiple) there are positive and significant effects of work discipline, work environment and work culture appraisal on the performance of employees work of employees of the Kantor Pelayanan Pajak Pratama Binjai. Thus the hypothesis proposed is accepted by the truth